2019
DOI: 10.1371/journal.pone.0223856
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean section delivery and childhood obesity in a British longitudinal cohort study

Abstract: BackgroundSeveral studies reported an association between Caesarean section (CS) birth and childhood obesity. However, there are several limitations in the current literature. These include an inability to distinguish between planned and emergency CS, small study sample sizes and not adjusting for pre-pregnancy body-mass-index (BMI). We examined the association between CS delivery and childhood obesity using the United Kingdom Millennium Cohort Study (MCS).MethodsMother-infant pairs were recruited into the MCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 58 publications
1
20
1
Order By: Relevance
“…Authors suggested there is no clinically relevant association between cesarean section and the development of obesity. The PIAMA study indicated an increased risk of obesity (OR = 1.7) [79] while a long-term prospective study conducted in the United Kingdom showed no significant correlation between elective cesarean section and both body mass index (BMI), as well as body fat percentage (BF%) in children [80]. The results of the remaining studies concerning the risk of developing other immune diseases are also ambiguous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors suggested there is no clinically relevant association between cesarean section and the development of obesity. The PIAMA study indicated an increased risk of obesity (OR = 1.7) [79] while a long-term prospective study conducted in the United Kingdom showed no significant correlation between elective cesarean section and both body mass index (BMI), as well as body fat percentage (BF%) in children [80]. The results of the remaining studies concerning the risk of developing other immune diseases are also ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of the search process is illustrated in Figure 2, as recommended by the PRISMA guidelines [90]. Due to sufficient data regarding the occurrence of respiratory tract infections, asthma, overweight/obesity as well as diabetes mellitus type 1, 16 articles [11,20,67,68,[70][71][72][73][74][75][76][77][78][79][80][81]85,86,88,89] were included in the meta-analysis. for those citations considered potentially relevant and assessed for eligibility by the two researchers.…”
Section: Study Selection Processmentioning
confidence: 99%
“…After reviewing the titles and abstracts, 43 relevant studies were obtained. After reading the full text, a total of 9 studies met the inclusion criteria and were used for final meta-analysis (16)(17)(18)(20)(21)(22)(23)(24)(25) (Figure 1).…”
Section: Characteristics Of the Selected Studiesmentioning
confidence: 99%
“…Furthermore, there was no difference in body fat percentage at 7 and 14 years old between infants born by planned cesarean section and those born by vaginal delivery. 9 A very large systematic review and meta-analysis conducted to investigate associations between mode of delivery and adult BMI, overweight, and obesity found that the mean BMI was 0.44 kg.m À2 greater in subjects delivered by cesarean section compared with those delivered vaginally. The increased odds of overweight and obesity > 20% applied to both genders.…”
Section: Cesarean Section and The Development Of Overweight And Obesitymentioning
confidence: 99%